Impact of Corporate Board Size on Firm Performance: Evidence from the Nepalese Banks - Padam Dongol (Journal of Corporate Finance Management and Banking System, 2023)
The purpose of this study is to determine the impact of corporate board size on the firm performance of Nepalese commercial banks. This study examines the banks that have directors less than seven on the board and directors equal to or more than 7 on the board, based on 8 years of data taken from the year 2013 to 2020. The study includes 27 banks as sample banks. The firm performance is measured by the Return on equity (ROE) and Return on assets (ROA). Corporate board size and firm performance are measured by using the Independent Sample t-test. The finding of the study shows that banks have less than seven directors on the board and banks have equal to or more than seven directors on the board have not found a significant impact on the firm performance of the commercial banks in Nepal.